ANALISIS KOREAN WAVE SEBAGAI BENTUK SOFT DIPLOMACY YANG EFEKTIF DIBIDANG KEBUDAYAAN - Lukita Perwita Sari (Journal of Diplomacy and International Studies, 2020)
Diplomacy is an instrument of achieving interests which is currently the most popular used. One type of diplomacy is soft diplomacy. South Korea is an example of a country that uses its soft diplomacy through Korean Wave as its medium. At present Korean Wave is no longer the stranger in society, especially among teenagers. South Korea succeeded in spreading Korean Wave not only in the Asian region, but also in Europe and America. Cultural diplomacy according to South Korea is able to be a tool for creating world peace because it is easily accepted by many people. The success of soft diplomacy is inseparable from the role of government policy. For this reason, in this study the author will discuss how to apply the soft diplomacy policy of the South Korean government through Korean Wave, and aims to explain the influence of the Korean Wave which might cause the spread of the influence of South Korean hegemony in the international sphere. In analyzing it, the writer uses a qualitative method in which the data obtained and compiled based on facts obtained through articles, journals, books, documents, online newspapers, and research reports from previous studies. From the data obtained shows that through soft diplomacy policies implemented by the South Korean government through the Korean Wave able to improve the image of South Korea in the international arena.